WILL DOMESTIC TOURISTS ADHERE TO HEALTH AND SAFETY PROTOCOL DURING POST COVID 19 PANDEMICS? EVIDENCE FROM INDONESIA. - Paromauli Manurung; Mas Wahyu Wibowo (Universitas Mercu Buana, 2022)
The purpose of this paper is to investigate the Indonesian domestic tourists’ protection behavior intention when travelling during the post-pandemic phase. This study employs the protective motivation theory (PMT) that involves the variables of perceived severity, perceived vulnerability, response efficacy, and self-efficacy to predict the protective behavior intention. Data were collected through 210 distributed questionnaires toward Indonesian domestic travelers. The collected data was analyzed by using SmartPLS. The Indonesian domestic travelers are mostly willing to comply with the health and safety procedure as imposed by the government when travelling during the post-pandemic phase. However, the respondents do not perceive themselves as vulnerable to the spread of covid 19 virus during traveling. The compliance toward the implementation of health and safety protocols and self confidence among Indonesian domestic tourists are high during traveling. Nevertheless, they do not consider themselves to be vulnerable with the covid 19. The results revealed that people are well-accustomed with the new normal to protect themselves from the exposure of covid 19 during traveling. The value of this study is the finding that the majority of Indonesian domestic tourists have adopted the safety and health protocol which increase their coping strategy in dealing with covid 19 as a threat during traveling.